Polymer microfluidic devices : thermo-mechanical properties - Ng, Albert Han Cai. (2009)
Microfluidics devices are of increasing importance as a platform for life sciences. With recent successes in lab-on-chips research, it will be brilliant if these Microfluidics devices could be manufactured using polymers. Using economical materials like polymers, the cost of producing these chips can greatly reduce, thus ensuing prompt detection of infectious diseases if these chips can be made accessible to the public, instead of the traditional method of sending blood sample to be tested in the laboratory compression rate. Cyclic Olefin Copolymer (TOPAS®) with its excellent chemical resistance property has been a polymer of interest in these recent years. TOPAS®, a relatively new material, with not many research been done on how this polymer’s properties changes when subject to different compression rate and temperature changes. For this project hot embossing technique is the area of interest for imprinting the microfluidics designs on the chips, compressive material testing was conducted to match the experiment closer to the manufacturing procedure. In this report the thermo-mechanical properties of amorphous thermoplastic polymers Cyclic Olefin Copolymer (TOPAS®) were studied by subjecting TOPAS® specimen of grade 8007 to a compression test at a controlled temperature environment between room temperature to 100°C and also at various engineering strain rate of 10-2/s, 10-3/s, 10-4/s and 3x10-4/s. Although this was a preliminary study, it revealed that experiments conducted was not able to achieve constant true strain rate condition with the equipment provided and readings taken without the extensometer does not show distinct strain hardening effects of the polymer at large strains. A preliminary study of comparing the effects of using Teflon sheet, Teflon spray and silicon spray (placed or sprayed between the surfaces of the specimen and the load platen) were also been scrutinized to observe if an improved result was produced. These materials were used to reduce the barreling effect in the compression experiment, hence to improve the result generated. Through the findings gathered, experiment could be designed to approximate the mechanical properties of TOPAS® by using the least square method to best fit the non linear strain rate into a linear procession of strain verse time.